KNOWLEDGE AND CARE OF ARTERIAL VENOUS FISTULA ACCESS IN HEMODIALYSIS PATIENTS: A CROSS-SECTIONAL STUDY - Lono Wijayanti; Hesmi Fitria Dewi; Yurike Septianingrum; Riska Rohmawati; Tata Mahyuvi (Nurse and Holistic Care, 2025)
Background: Arteriovenous fistula (AVF) access is vital for patients undergoing hemodialysis therapy. Proper care of AVF greatly affects the continuity of fistula function and prevents complications such as infection and thrombosis. Objective: This study was to determine the relationship between knowledge and management of arteriovenous fistula access in hemodialysis patients. Methods: This study is a correlational analysis with a cross-sectional design. The study population included all dialysis patients, totaling 200 respondents. The sample size was 160 respondents who were randomly selected using the simple random sampling method. Questionnaires were used to collect information, which was then analyzed using Spearman's Rank correlation test. Results: The results showed that 57.5% of the 160 respondents had insufficient knowledge, and 60% lacked in arteriovenous fistula (cimino) care. The Spearman test results showed a p-value of 0.000 and a correlation of 0.709. Conclusion: Patients with good knowledge tend to perform AV fistula care more appropriately and consistently.